The control and performance of Li4Mn5O12 and Li2MnO3 phase ratios in the lithium-rich cathode materials. (1st February 2016) - Wang, Di; Wang, Xianyou; Yu, Ruizhi; Bai, Yansong; Wang, Gang; Liu, Meihong; Yang, Xiukang
Highlights: Li-rich cathode materials with different layered-spinel ratios are synthesized. Gradient calcination processes are designed to control the phase ratios. The calcination time and temperature jointly influence the phase ratios. The electrochemical performances with various phase components are studied. Abstract: Lithium-rich (Li-rich) cathode materials with different layered-spinel phase ratios are successfully synthesized by solvothermal and gradient calcination processes. The structure and electrochemical performances of the lithium-rich cathode materials with different layered-spinel phase ratios are investigated by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), high rate transmission electron microscopy (HRTEM), fast Fourier transformation (FFT) and electrochemical charge-discharge measurements. The results show that the calcination time and calcination temperature in gradient calcination processes jointly influence the phase ratios of the layered Li2 MnO3 and spinel Li4 Mn5 O12 in the hybrid structure. Moreover, the spinel phase can lead to an excellent coulombic efficiency and cycle stability, while the layered phase will provide a high capacity. The materials with different layered-spinel phase ratios prepared in different gradient calcination processes show apparently different electrochemical performances, e.g., the maximum discharge capacity of the sample reaches 297 mAh/g at 0.1 C, it even exhibits high capacity retention of 90.6% after 200 cycles at 0.5 C. Furthermore, the temperatures at 750 and 800 °C are considered to be the suitable selection for the gradient calcination process. The spinel phase can profitably grow at 750 °C, and the layered phase is produced at 800 °C.